IMPLEMENTATION TEAM ASSISTED INDIVIDUALIZATION LEARNING MODEL ASSISTED BY WORKSHEET BASED ON CONTEXTUAL TEACHING AND LEARNING TO IMPROVE STUDENT LEARNING OUTCOMES - Puspita Dwi Ratnasari; Mohammad Budiyanto (Jurnal Penelitian Pendidikan IPA, 2020)
AbstractThe purpose of this research was to describe the increase in learning outcomes through implementation of Team Assisted Individualization learning model assisted by student worksheet based on Contextual Teaching and Learning  on human circulatory system. This research was used a One Group Pretest-Posttest Design. This research was conducted on 36 students of SMP Negeri 32 Surabaya. The learning activity in this research got 4 in modus which belongs to good criteria. The results of learning outcomes in the form of knowledge competencies in this research was obtained from the results of the N-Gain test which showed that 64% of students belong to the high category and 36% of students obtained scores that belong to the medium category. The learning outcomes in the form of students knowledge competencies were known from the students pretest and posttest score. The results of the student posttests increased after the implementation of Team Assisted Individualization learning model assisted by student worksheet based on Contextual Teaching and Learning. The results in the form of learning skills competencies were obtained an average score of 85 which belongs to good criteria at the first meeting  and 87 which belongs to very good criteria at the third meeting. This research received 96% positive responses from the students. The conclusion of this research is that the implementation of Team Assisted Individualization learning model assisted by student worksheet based on Contextual Teaching and Learning  on human circulatory system material able to improve students learning outcomes.